Las Misiones Jesuíticas en la historiografía argentina entre la segunda mitad del siglo XIX y principios del siglo XX - Mari, Óscar Ernesto (Revista Complutense de Historia de América, 2006)
During a long period in Argentina, at least until half-full of century XIX, the knowledge of the colonial past as soon as it advanced and it was supported in old chronicles and it was dominated by an increasing Hispanic prejudice. Although there were attempts of change during second half of century XIX and principles of the XX, this prejudice and other limitations of methodologic order continued restricting the objective treatment of good part of the colonial stage, specially of those subjects that for a long time were controversial, like for example the concerning ones the action of the Jesuits in the River plate scope. Indeed this subject caused different controversies and approaches according to the ideas, and the profile of each one of the authors whom the question approached. In the following pages it will be tried to show the appreciations that have deserved same on the part of some emblematic historians in the Argentina historiography of aims of century XIX and principles of the XX.